Thermal decomposition of vitamin C: An evolved gas analysis−ion attachment mass spectrometry study - Juhász, Márta; Kitahara, Yuki; Fujii, Toshihiro (Food Chemistry, 2011)
► We studied the real time non-isothermal decomposition of vitamin C. ► Evolved gas analysis−ion attachment mass spectrometry (EGA−IAMS) was utilised. ► We could observe dehydro-l-ascorbic acid as a decomposition product for the first time. ► Our results were compared with those obtained by pyrolysis-GC−MS. ► Quantitative and qualitative differences between the products were found. Evolved gas analysis−ion attachment mass spectrometry (EGA−IAMS) was utilised to study the real-time non-isothermal decomposition of vitamin C. Dehydro-l-ascorbic acid, which has until this study been undetectable from the solid phase degradation of vitamin C, was observed as a decomposition product. While it is an important compound because it possesses some biological activity, dehydro-l-ascorbic acid is difficult to measure due to its chemical instability. In the present study using EGA−IAMS, we were able to detect dehydro-l-ascorbic acid from the thermal degradation of vitamin C. Our EGA−IAMS results obtained from the thermal decomposition of vitamin C were compared with a previous study employing pyrolysis-gas chromatography−mass spectrometry (Pyr-GC−MS). The observed quantitative and qualitative differences of the pyrolysis products obtained by the two techniques (EGA−IAMS vs. Pyr-GC–MS) are in part due to the difference in transportation time of the products out of the pyrolysis chamber.